Asthma and delirium episodes during hospitalization. Issue 2 (9th June 2021) - Bozek, Andrzej; Fiolka, Rafał; Zajac, Magdalena
Abstract: Background: Delirium incidences during hospitalization are an important problem in elderly patients. The problem of delirium episodes in patients with obstructive disease during hospitalization was investigated. Material and Methods: From a total of 37, 156 subjects, the following were randomly selected: 32, 261 patients with asthma, 4896 with chronic obstructive pulmonary disease (COPD), and 5455 without obstructive disease. Their ages ranged from 65‐95 years, and they were hospitalized between 2006 and 2015. Delirium incidences were monitored based on the International Classification of Disease (ICD)‐10 codes and medical documentation. Results: The delirium episodes during all hospitalizations were independently associated with asthma (odds ratio [OR] = 2.91, confidence interval [CI] = 1.62‐5.84), with severe type of asthma (OR = 4.24, CI = 1.94‐8.93), partim controlled asthma (OR = 3.1, CI = 1.29‐8.46), and uncontrolled asthma (OR = 4.88, CI = 2.12‐9.42). It was comparable with COPD as follows: all incidences of delirium during hospitalization (OR = 3.17, CI = 1.42‐7.23) or severe COPD (III degree OR = 5.15, CI = 2.01‐13.69). Elderly patients with asthma with uncontrolled or partially controlled asthma with a coincidence of advanced age, dementia, or smoking had a greater predisposition to delirium episodes, particularly after surgery. Additionally, delirium incidence caused death more frequently in patients with asthma than in those with COPD. Conclusion: Elderly patients with asthma have a higher risk of delirium episodes during any hospitalization, and, frequently, it ends in death.